A STUDY ON INFLUENCE OF SERVICE QUALITY DIMENSIONS ON CUSTOMER LOYALTY WITH SPECIAL REFERENCE TO RETAIL BANKS IN CHENNAI - N., Sornakumari; G., Yogeswaran; P., Muthu Ganeshwari; K., Hindja Priyaa; A., Kalavathi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this research is to look into the link between service quality and client satisfaction and employee satisfaction and the ways through which service firms can improve and oversee the operation of delivering quality standards to their clients. For this function, the study analyses the issue of service quality on customer satisfaction and employee satisfaction by discussing their relationship. The client service is seen as an inbuilt component of any aspect of the industry and it determines the future of any governing body. The rapid advances in engineering based systems related to internet are leading fundamental ways in how different organizations interact. This applies same in relation of the banks with its client. In different services industries the relationship between client satisfaction and service attributes have been hard to identify because services nature is intangible. This article describes the influencing factor on customer loyalty in the selected area. The influence of the service quality dimensions on customer loyalty is estimated through the Linear multiple regression analysis.